Stakeholders' Perspectives on Microplastics in Sludge Applied to Agricultural Land - Zilinskaite, Emilija; Futter, Martyn; Collentine, Dennis (Frontiers in Sustainable Food Systems, 2022)
Microplastics (MPs) input to agricultural lands from wastewater and sewage sludge reuse in Europe has been estimated to be between 65,000 and 230,000 tonnes/year making the farm environment one of the major receptors and, possibly, environmental reservoir of MPs. In Sweden there have been ongoing discussions since 1994 about environmental and health effects of sewage sludge application to agricultural lands. This debate on sludge use focused initially on heavy metals, then moved on to pharmaceutical residuals and currently has turned to MPs. In spite of the limited scientific information about environmental impacts of MPs in soils, governmental approval in Sweden to allow increased spreading of sludge on productive agricultural lands is moving forward. To study individual perceptions of the risks, interviews were conducted in 2020 with Swedish stakeholders who in some way work with the issue of sludge management. The results of these interviews provide an indication of not only how environmental risk information is interpreted by representatives from different sectors but also the degree to which perceived risks may shape environmental policy.